Legumain is a paracrine regulator of osteoblast differentiation and mediates the inhibitory effect of TGF-β1 on osteoblast maturation - Forbord, Karl Martin; Lunde, Ngoc Nguyen; Bosnjak-Olsen, Tatjana; Johansen, Harald Thidemann; Solberg, Rigmor; Jafari, Abbas (Frontiers in Endocrinology, 2024)
Abstract Transforming growth factor-beta 1 (TGF-β1) is a critical regulator of skeletal homeostasis and has diverse effects on osteoblastogenesis. To date, the mechanisms behind the intriguing inhibitory effect of TGF-β1 on osteoblast maturation are not fully understood. Here, we demonstrate a novel mechanism by which TGF-β1 modulates osteoblast maturation through the lysosomal protease legumain. We observed that addition of TGF-β1 to osteogenic cultures of human bone marrow derived mesenchymal stromal (stem) cells enhanced legumain activity and secretion, in-spite of decreased legumain mRNA expression, suggesting post-transcriptional regulation. We further showed that osteogenic cells internalize and activate prolegumain, associated with inhibited osteoblast maturation, revealing legumain as a paracrine regulator of osteoblast maturation. Interestingly, TGF-β1 treatment exacerbated legumain internalization and activity, and showed an additive effect on legumain-induced inhibition of osteoblast maturation. Importantly, pharmacological inhibition of legumain abolished the inhibitory effect of TGF-β1 on osteoblast maturation. Our findings reveal that TGF-β1 inhibits osteoblast maturation by stimulating secretion and activity of endogenous legumain, as well as enhancing internalization and activation of extracellular prolegumain. Therefore, our study provides a deeper understanding of the complex regulation of osteoblastogenesis and unveils a novel TGF-β1-legumain axis in regulation of osteoblast maturation, offering novel insights for possible therapeutic interventions related to bone diseases associated with aberrant TGF-β1 signaling.